Tomb of Pope Alexander VIII Ottoboni (b.Venice, 241st Pope, 1679-81) - ROSSI, Angelo de
relief of the base, depicting canonization of five saints:S. Giovanni da S. Facondo, S. Giovanni da Capistrano, S. Pasquale Baylon, S. Giovanni di D